Ragam Ungkapan Damai dalam Al-Qur’an - Miss Kholeefah Jukeng; Zainuddin Zainuddin (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2018)
Islam has come as a religion that carries a mission of peace and strictly forbids mankind to do tyranny. As social beings, humans must follow certain provisions and regulations if they live and are in the midst of society. The word